Incentive Zakat Agency Mechanism, a Comparison between Indonesia and Malaysia - Dodik Siswantoro; Abdul Ghafar Ismail; Agus Munandar; Nurzaman, Mohammad Soleh (International Journal of Islamic Business and Economics (IJIBEC), 2021)
the objective of the research is to compare the incentive zakat agency mechanism between Indonesia and Malaysia. In Indonesia, private institutions are permitted to collect zakat and have the agency to support zakat collection, while in Malaysia only state institution collects zakat. To enhance zakat fund collectability, they need agencies located in specific institutions. However, both countries share a similar mechanism of incentive zakat agency allocation. The method of the research is based on a qualitative study. Some respondents are questioned and interviewed on a specific topic of incentive zakat agency mechanism. The result shows that the agency mechanism in private zakat institutions in Indonesia is more flexible than Malaysia. The agency is authorized to get zakat allocation to be disbursed to surrounding zakat recipients and develop the allocation report. On the other hand, a zakat rebate can be a supporting factor for Muslims to pay zakat more in Malaysia than in Indonesia.